Apollo 8 : the thrilling story of the first mission to the Moon - Kluger, Jeffrey (Henry Holt and Co., 2017)
Recounts the bold but dangerous mission to secure America's position as the first nation to reach the moon, revealing the dangers endured by its crew and the ways the mission brought renewal to a country ravaged by assassinations and war.